Tuberculosis in Children: New diagnostic Blood Tests. Issue 4 (2010) - Kakkar, F; Allen, UD; Ling, D; Pai, M; Kitai, IC
Abstract : The interferon-gamma-release assays were developed to overcome the pitfalls and logistic difficulties of the tuberculin skin test (TST) for the diagnosis of latent tuberculosis infection (LTBI). These blood tests measure the in vitro production of interferon-gamma by sensitized lymphocytes in response to Mycobacterium tuberculosis -specific antigens. Two interferon-gamma-release assays are registered for use in Canada: the QuantiFERON-TB Gold In-Tube assay (Cellestis Inc, Australia) and the T.SPOT–TB test (Oxford Immunotec, United Kingdom). Evaluation of these tests has been hampered by the lack of a gold standard for LTBI, and limited paediatric data on their use. It appears that they are more specific than the TST, and may be useful for evaluating TST-positive patients at low risk of true LTBI. Moreover, they may add sensitivity if used in addition to the TST in immunocompromised patients, very young children and close contacts of infectious adults. A summary of these tests, their limitations and their application to clinical paediatric practice are described.